Program Pengabdian Pendidikan Agama Islam dan Bakti Sosial untuk Pembinaan Spiritual Warga Binaan di Lapas Perempuan III Mataram - Dewi Urifah; Niswatun Hasanah; Mushbihah Rodliyatun (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2026)
This research focuses on the importance of the Islamic religious education and social service devotion programs in nurturing the spiritual well-being of female inmates at Lapas Perempuan III Mataram. This institution is the only female correctional facility in West Nusa Tenggara, committed to establishing a corruption-free integrity zone. Inmates at this facility face various complex challenges, including the loss of dual roles as mothers, wives, and family members, compounded by social stigma that exacerbates their mental and psychological conditions. These conditions necessitate a holistic approach integrating religious education and social service activities to support their rehabilitation and social reintegration processes. The service program combines Islamic religious education discussions and social service activities as its main methods. The discussions on Islamic religious education are designed to enhance the religious knowledge of Muslim inmates, address their concerns, and provide moral support. Additionally, social service activities such as the distribution of Friday Alms packages help alleviate the material burdens of inmates and strengthen relationships between them and prison staff. This combination of methods is expected to provide comprehensive support encompassing spiritual, emotional, and material aspects, thereby creating a more conducive environment for the rehabilitation and social reintegration of female inmates at Lapas Perempuan III Mataram.